2018
DOI: 10.1002/cpdd.465
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Target Attainment of Ceftobiprole in Asian and Non‐Asian Subjects

Abstract: Ceftobiprole is a broad-spectrum cephalosporin. The objective of this study was to test the hypothesis that the pharmacokinetics (PK) and exposure of ceftobiprole in Asian subjects are similar to those in non-Asian subjects. Three approaches were followed. The first compared the individual PK estimates between the 2 subgroups derived from a population PK model previously built. Next, it was determined whether "Asian subject" was a significant covariate. Finally, a pharmacodynamic analysis was performed by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…A recent population pharmacokinetic/pharmacodynamic analysis demonstrated that at the standard ceftobiprole dose of 500 mg every 8 h as a 2-h infusion no pharmacokinetic or pharmacodynamic differences existed between Asian and non-Asian subjects, considering that, at a pharmacodynamic target of 60% t> MIC of the dosing interval, more than 90% of the population was adequately exposed in both subgroups [36].…”
Section: Pharmacological Properties Of Ceftobiprolementioning
confidence: 99%
“…A recent population pharmacokinetic/pharmacodynamic analysis demonstrated that at the standard ceftobiprole dose of 500 mg every 8 h as a 2-h infusion no pharmacokinetic or pharmacodynamic differences existed between Asian and non-Asian subjects, considering that, at a pharmacodynamic target of 60% t> MIC of the dosing interval, more than 90% of the population was adequately exposed in both subgroups [36].…”
Section: Pharmacological Properties Of Ceftobiprolementioning
confidence: 99%
“…Racial homogeny of the study population may also limit applicability of the results, although this is mitigated by the fact that the pathophysiology of pneumonia does not differ between racial groups and the pharmacokinetic profile of ceftobiprole is not altered by ethnicity. 21 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, no significant differences in the pharmacokinetics or pharmacodynamics of ceftobiprole 500 mg administered every 8 h as a 2-h intravenous (iv.) infusion were observed [22]. Median clearance was 4.82 l/h (range, 2.12-10.47) in Asian patients and 4.97 l/h (range, 0.493-20.6) in non-Asian patients (p = 0.736), and no significant difference was reported in terms of exposure, with bioequivalence indicated via a geometric mean ratio for the area under the unbound drug concentrationtime curve of 1.022 (90% CI: 0.91-1.15) [22].…”
mentioning
confidence: 97%
“…infusion were observed [22]. Median clearance was 4.82 l/h (range, 2.12-10.47) in Asian patients and 4.97 l/h (range, 0.493-20.6) in non-Asian patients (p = 0.736), and no significant difference was reported in terms of exposure, with bioequivalence indicated via a geometric mean ratio for the area under the unbound drug concentrationtime curve of 1.022 (90% CI: 0.91-1.15) [22]. A probability of target attainment was >90% in both Asian and non-Asian patients for broad-spectrum coverage with unbound drug concentration exceeding a conservative minimum inhibitory concentration of 4 mg/l for 60% of the dosing interval [22].…”
mentioning
confidence: 97%
See 1 more Smart Citation